Research on the health of and interventions for family caregivers of people with dementia: a bibliometric analysis of research output during 1988–2018 - Hui Shi; Chen Mao; Jinling Tang; Huiying Liang (BMC Geriatrics, 2020)
Abstract Background Dementia is a serious and growing health problem, and since most people with dementia live at home, caring responsibilities generally fall on family members. Caregivers are often inadequately supported by formal health services and have poorer psychological and physical health. Our study aimed to compare the contributions of publications from different countries, institutions and authors and present a bibliometric analysis to determine the hotspots and trends in research concerning the health of and interventions for family dementia caregivers. Methods Studies published during 1988–2018 were extracted from the Science Citation Index Expanded of the Web of Science. Each abstract of publications was evaluated to obtain the basic information. A bibliometric analysis was used to evaluate the number or cooperation networks of publications, countries, institutions, journals, citations, authors, references, and keywords. The resulting articles were analyzed descriptively, and the publication keywords were visualized using VOSviewer. Results Five hundred forty-two articles were identified. The annual number of relevant publications has steadily increased since approximately 2006. The USA has the highest number of publications (36.2%), followed by the UK (12.9%). China entered the field late, but research conducted in China has rapidly developed. The most productive institution, journal, and author in this field are University College London, the Journal of the American Geriatrics Society, and Orrell M from the UK, respectively. A co-occurrence analysis of the keywords reveals a mainstream research focus on burden, depression, quality of life, and corresponding interventions for people with dementia caregivers. The keywords “psychosocial intervention”, “long-term”, “e-learning/online”, “communication”, and “qualitative research” reflect the latest hotspots, appearing in approximately 2017–2018. Conclusion Our study details the performance statistics, main topics and trends research on the health of and interventions for dementia caregivers from 1988 to 2018 and provides a comprehensive analysis.